Resource partitioning among avian predators of the Arctic tundra. Issue 12 (7th October 2020) - Seyer, Yannick; Gauthier, Gilles; Fauteux, Dominique; Therrien, Jean‐François
Abstract: Interspecific competition can play a key role in structuring ecological communities. The Arctic tundra is a low productivity ecosystem supporting simple food webs, but several predators often feed on the same prey species, lemmings, known for their large‐amplitude population fluctuations. We examined mechanisms involved in reducing intra‐guild competition and allowing coexistence of four avian predators (snowy owls, glaucous gulls, rough‐legged hawks and long‐tailed jaegers) feeding on a pulsed resource (brown and collared lemmings). We compared the size and species of prey consumed by predators to see if resource partitioning occurred. We also verified if spatial segregation in nesting areas could be another mechanism allowing coexistence. Finally, we tested if the absence of the snowy owl, a dominant and irruptive species, triggered a competitive release on the smallest predator, the jaeger, with respect to prey size and nesting area used. We monitored the breeding of predators and lemming abundance over a 14‐year period on Bylot Island, Canada. We mapped their nesting sites and collected regurgitation pellets to recover lemming mandibles, which were used to infer prey species and size. The size of lemmings consumed varied among species with the largest predators consuming the largest lemmings and the smallest predators consuming the smallest lemmings. All predators consumed more collared than brown lemmings compared to their availability although owls and jaegers consumed relatively more brown lemmings compared to gulls and hawks. Jaegers consumed larger lemmings in the absence of owls than in their presence, suggestive of a short‐term competitive release. We found moderate to low overlap in nesting areas among predators and no evidence of their expansion in the absence of owls, suggesting that spatial distribution is caused by species‐specific habitat preferences. The main mechanism to partition food resources among these avian predators is spatial segregation, and secondarily prey size and species. However, we found evidence that food competition is still present and leads to a niche shift in the smallest predator of the guild. Interspecific competition may thus be a pervasive force in simple, low productivity food webs characterized by pulsed resources. Abstract : In contrast to the conventional wisdom in ecology, the authors found that competition was more intense when resources were abundant rather than scarce. This is due to the irruptive behaviour of the most dominant predator which occurs in the years of high prey densities while other predator species also increase their breeding effort. Résumé: La compétition interspécifique peut jouer un rôle clé pour structurer les communautés écologiques. La toundra arctique, un écosystème peu productif, est l'hôte d'un réseau trophique simple où plusieurs prédateurs s'alimentent sur les mêmes proies, les lemmings, connus pour leurs cycles d'abondance de grande amplitude. Nous avons étudié les mécanismes impliqués dans la réduction de la compétition intra‐guilde permettant la coexistence de quatre espèces de prédateurs aviaires (harfang des neiges, goéland bourgmestre, buse pattue, labbe à longue queue) qui se nourrissent de ressources fluctuantes (lemmings bruns et variables). Nous avons comparé la taille et les espèces des proies consommées par chaque prédateur afin d'évaluer si une ségrégation se produisait. Nous avons aussi vérifié si une ségrégation spatiale dans les aires de nidification permettait la coexistence de ces prédateurs. Finalement, nous avons testé si l'absence de harfangs, une espèce dominante et irruptive, initiait un relâchement de la compétition sur le plus petit prédateur, le labbe, en changeant la taille de ses proies et de son aire de nidification. Nous avons suivi la reproduction des prédateurs et l'abondance des lemmings pendant 14 ans sur l'Île Bylot (Canada). Nous avons cartographié les nids et récolté des pelotes de régurgitation pour mesurer la taille des mandibules de lemmings et inférer la taille et l'espèce consommées. La taille des lemmings consommés variait selon les espèces, les plus grands prédateurs consommant les plus gros lemmings et le plus petits prédateur les plus petits lemmings. Tous les prédateurs consommaient plus de lemmings variables comparativement à leur disponibilité, bien que les harfangs et les labbes consommaient relativement plus de lemmings bruns que les goélands et les buses. Les labbes ont consommé des lemmings plus gros en l'absence de harfangs qu'en leur présence, suggérant un relâchement de la compétition à court‐terme. Nous avons trouvé un chevauchement modéré à faible dans les aires de nidification entre les prédateurs et aucune évidence de leur expansion en l'absence de harfangs. Ceci suggère que la distribution spatiale est causée par les préférences d'habitat de chaque espèce. La ségrégation spatiale constitue le principal mécanisme menant au partage de la ressource alimentaire entre les prédateurs aviaires et, secondairement, la taille et les espèces de proies. Cependant, nous avons trouvé des évidences que la compétition alimentaire est toujours présente et conduit à un changement de la niche chez le plus petit prédateur de la guilde. La compétition interspécifique pourrait donc être une force omniprésente dans les réseaux trophiques simples et peu productifs caractérisés par des ressources fluctuantes.